Sharing School Leadership: Principalship Empowerment or Relegation? - Amzat, Ismail Hussein (Springer Nature Singapore Pte Ltd, 2017)
In current developments concerning school leadership, the assumption of a single individual taking responsibility for and controlling every single aspect of running a school from the most crucial concern to the most trivial has been put on trial. In the modern approach to school administration, a distributed leadership model is proposed and introduced as a source of empowering teachers towards collective responsibility, creating accountability and developing a sense of encouragement for participating in the decision-making process. However, with the application of these theories in school sectors, the question remains as to whether the implications of sharing or distributing school leadership power were considered when the model was first created. In other words, at a minimum deep deliberation is required during the application due to the potential impacts or repercussions that sharing or distributing leadership and power might have on the role and position of principalship. This paper sheds light on the effectiveness of distribution and shared leadership in a school setting, examining the level of power to be shared, and the extent of trust and professional training given to teachers prior to power distribution